KESIAPAN DAN STRATEGI GURU MUDA DALAM MENGEMBANGKAN KETERAMPILAN ABAD 21 DI SEKOLAH DASAR BERBASIS DIGITAL - Adinda Febriza; Utari Oktadika; Yunda Sekar Wangi; Rifqa Gusmida Syahrun Barokah (CV. ADIBA AISHA AMIRA, 2026)
This descriptive qualitative study aims to analyze the level of readiness and strategies of young teachers in Pecanbal in developing 21st-century competencies, particularly within the 4C framework (critical thinking, communication, collaboration, and creativity). This study specifically focuses on the use of digital infrastructure in elementary schools by teachers with less than five years of experience. Data were collected through in-depth semi-structured interviews conducted with six participants selected using purposive sampling. The data analysis process followed the Miles and Huberman model (reduction, presentation, and drawing of conclusions) and was verified through source triangulation. The research findings highlight conflicting realities in the field. Although young teachers demonstrate high technical proficiency in using digital devices, there are still significant shortcomings regarding pedagogical integration. These technical skills have not yet been fully integrated with effective pedagogical strategies to maximize the potential of technology in learning. These findings confirm that proficiency with digital tools does not always guarantee success in developing students’ competencies. Therefore, to ensure that young teachers’ technical preparation leads to significant and systematic pedagogical innovation in the classroom, there is a need for ongoing reinforcement of aspects related to technological, pedagogical, and content knowledge (TPACK).